Asset Based Village Development, A Good Practice from Desa Banyuurip Ujungpangkah, Kabupaten Gresik in Maintenance Mangrove Area as Touris Destination - Achmad Room Fitrianto; Andriani Samsuri (Universitas Muhammadiyah Surakarta, 2022)
This study analyses the effort of the Banyuurip village in enhancing their potencies and asset in preserving mangrove area. The purpose of this writing to portray the involvement of the youth in sustains local tourism development. The parameters used to determine the degree of public participation in the development planning phase are the involvement in problem identification, objective formulation, and decision making related to the development of the local tourist attraction. This paper analysed the five strategies of Banyuurip village government and their counterpart in creating sustainable tourism system. The SWOT analyses employ to analyse the five elements of strategies in creating sustainable tourism system. This approach is believed able to provide an holistic analysis in Community Based Tourism (CBT) development. The problems faced by the Banyuurip tourism community in managing their local tourist destination are lack of adequate human resources, limited of public facilities, limited financial support, lack of regulation that support the CBT, inter-organizational coordination problems, conflict of interest among group of community, and property ownership. This writing found that the position of the village leader both formal and informal leader is significant in CBT Development. However, the sustainable tourism it self requires the government political will in the development of CBT.